OPTIMIZATION OF “PAS COFFEE ROASTERY” WORK ACTIVITIES USING THE TOTAL QUALITY MANAGEMENT (TQM) CONCEPT AT CLASS IIA METRO PRISON - Nasyt, Muhammad Farhan; Indahdewi, Lauditta (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The research conducted to discuss the optimization of work activities at "PAS Coffee Roastery" using the Total Quality Management (TQM) concept in Class IIA Metro Prison. The study used a qualitative method with 5 informants as research subjects, with primary and secondary data sources obtained from Class IIA Metro Prison. Data were collected using interview techniques, observation, and document studies, and then the data were analyzed by reducing data, presenting data, and drawing conclusions. The results of the study are that the optimization of work activities at "PAS Coffee Roastery" is still running as it should, and it is necessary to add an application using a concept called TQM to be able to optimize the work activities of Pas Coffee Roastery. The obstacles experienced are that there must be training provided for prisoners and officers by experts in their fields on an ongoing basis, then the addition of officers in the work activity section to be more effective and efficient, then the addition of equipment that has a larger scale in roasting coffee beans and also a more adequate place, and finally there must be officers who are competent and experts in the field of marketing. Keywords: Work Activities; TQM; Optimization; Prisoners